2020
DOI: 10.1098/rsos.200640
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of graphene oxide nanosheet against multidrug resistant superbugs isolated from infected patients

Abstract: Graphene oxide (GO) is a derivative of graphene nanosheet which is the most promising material of the decade in biomedical research. In particular, it has been known as an antimicrobial nanomaterial with good biocompatibility. In this study, we have synthesized and characterize GO and checked its antimicrobial property against different Gram-negative and Gram-positive multidrug drug resistant (MDR) hospital superbugs grown in solid agar-based nutrient plates with and without human serum through the utilization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(43 citation statements)
references
References 83 publications
0
36
1
Order By: Relevance
“…The silver nanoparticles work by generating vast amounts of silver ions, which influence the permeability of the cell membrane and help to inhibit energy transfer through the transport chain of electrons. In addition, microbial cell damage to DNA [ 336 , 337 , 338 ] has also been identified. Zinc oxide nanoparticles are another type of nanoparticle which grows in the cells and emit Zn +2 ions there.…”
Section: Nanomaterialsmentioning
confidence: 99%
“…The silver nanoparticles work by generating vast amounts of silver ions, which influence the permeability of the cell membrane and help to inhibit energy transfer through the transport chain of electrons. In addition, microbial cell damage to DNA [ 336 , 337 , 338 ] has also been identified. Zinc oxide nanoparticles are another type of nanoparticle which grows in the cells and emit Zn +2 ions there.…”
Section: Nanomaterialsmentioning
confidence: 99%
“…The antimicrobial property of graphene‐based materials has been demonstrated in many publications, e.g., it was reported that GO can treat multiple drug‐resistant bacterial superbugs isolated from infected patients, and its efficiency is much higher than some conventional antibiotics, offering hope for a last‐line antibiotic to address the global crisis of antimicrobial resistance. [ 96 ] However, it has also been reported to have no antimicrobial properties in some studies. [ 97 ] In fact, there are a big number of parameters that influence the antimicrobial testing results, which could explain the diverse results reported in the literature.…”
Section: Intrinsic Reactivity Of Go and Its Applications: The Role Ofmentioning
confidence: 99%
“…The structure of the external coatings of bacteria differs between bacterial species, which has an impact on the cell capacity to tolerate stress such as ROS-related lipid peroxidation and membrane disruption by sharp edges of graphene flakes. In comparison to Gram-negative bacteria, Gram-positive lacking the outer membrane are more sensitive to contact with sharp edges of graphene flakes [ 42 , 45 ].…”
Section: Resultsmentioning
confidence: 99%